Histone Signatures Predict Therapeutic Efficacy in Breast Cancer - Shamim A. Mollah; Shankar Subramaniam (IEEE Open Journal of Engineering in Medicine and Biology, 2020)
Objective: Regulatory abnormalities caused by chromatin modifications are being increasingly recognized as contributors to cancer. While many molecularly targeted drugs have the potential to revert these modifications, their precise mechanism of action in cellular reprogramming is not known. Methods: To address this, we introduce an integrated phosphoprotein-histone-drug network (iPhDNet) approach to generate “global chromatin fingerprints of histone signatures.” The method integrates proteomic/phosphoproteomic, transcriptomic and regulatory genomic data to provide a causal mechanistic network and histone signatures of drug response. Results: We demonstrate the utility of iPhDNet in identifying H3K27me3K36me3 histone mark as a key fingerprint of response, mediated by chromatin remodelers BRD4, NSD3, EZH2, and a proto-oncogene MYC when treated with CDK inhibitors. Conclusions: We construct a regulatory network of breast cancer response to treatment and show that histone H3K27me3K36me3 status changes, driven by the BRD4/MYC pathway, upon treatment with drugs are hallmarks of response to treatment.